Effect of Dietary Protein Level and Protein to Energi Ratio on the Growth of Swimming Crab Portunus pelagicus - Serang, A. Malik; Suprayudi, M. Agus; Jusadi, D.; Mokoginta, I. (Indonesian Society of Scientific Aquaculture (ISSA), 2007)
The extending of protein and energy of the Swimming crab should be on certain limit that could be give maximum growth. The objective of this research are to determine of the protein level and optimum energy ratio of protein (C/P) at rajungan (Portunus pelagicus). The Crab-5 (C-5) stage used in the experiment, maintained in the topless (volume of 2 liters), with density of 1 crab/glass. There were seven of the experimental diets namely A (protein of 30%; C/P of 8 kkal), B (30%; 9.5), C (35%; 8), D (35%; 9.5), E (40%; 8), F (40%; 9.5) and G (45%; 8) with extending of food are 5 time of daily. Complete randomize design with 2 of factor and 3 of replication use in the experiment. The results of this experiment showed that interaction of the protein level and the energy ratio of protein is influence to the growth rate of daily and retention of lipid. The D is the best in give of the growth rate of daily, the consumption of food, the retention of protein, and the frequency of moulting (P